2012
DOI: 10.1007/s10585-012-9556-3
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial ultrasound-guided transbronchial needle aspiration in the diagnosis of intrathoracic lymph node metastases from extrathoracic malignancies

Abstract: Intrathoracic lymph node enlargement is a common finding in patients with extrathoracic malignancies. Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a technique that is commonly used for lung cancer diagnosis and staging but that has not been widely investigated for the diagnosis of enlarged mediastinal and lobar lymph nodes in patients with extrathoracic malignancies. We conducted a retrospective study of 117 patients with extrathoracic malignancies who underwent EBUS-TBNA for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Additionally, NPV was 88.3% in this study, which was similar to the results of other studies that reported rates of between 76% and 86.9% (17,19,27,28). Five cases were diagnosed as malignancy after mediastinoscopy, although EBUS-TBNA results were reported as benign.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, NPV was 88.3% in this study, which was similar to the results of other studies that reported rates of between 76% and 86.9% (17,19,27,28). Five cases were diagnosed as malignancy after mediastinoscopy, although EBUS-TBNA results were reported as benign.…”
Section: Discussionsupporting
confidence: 89%
“…It is a relatively simple and safe method to see beyond the bronchial tree. The importance of TBNA in the diagnosis of lung cancer and mediastinal lymph node staging has been widely accepted [5][6]. However, only few studies have been conducted on the importance of TBNA in the diagnosis and differential diagnosis of mediastinal lesions in patient with recurrent ovarian cancer and without lung abnormalities [7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Sanz-Santos et al (20), in their recently published study that included 117 patients, similarly reported that the sensitivity of EBUS-TBNA in the diagnosis of extrathoracic malignancy with mediastinal metastases was 86.4% and NPV was 75%. In a recently published review, all studies published up to 2014 concerning the value of EBUS-TBNA in determining extrathoracic malignancies with intrathoracic metastases were investigated, and a total of six studies that had a minimum of 30 patients and at least 6 months follow-up were included in the meta-analysis.…”
Section: N (%)mentioning
confidence: 98%
“…Nevertheless, there are still a few studies demonstrating the use of EBUS-TB-NA in determining the intrathoracic metastases of extrathoracic malignancies (12,(17)(18)(19)(20). In a retrospective study including 92 patients, the sensitivity of EBUS-TBNA was 85% (17); a similar study, in which 161 patients were included, found the sensitivity to be 87% and NPV to be 73% (12).…”
Section: N (%)mentioning
confidence: 99%